The Degree of Implementation of Sustainable Leadership by Jeddah School Principals and its Relationship to Organizational Commitment from the Teachers' Point of View (The International Journal of Educational Sciences and Arts, 2024)
The aim of the research is to identify the degree of implementation of sustainable leadership by school principals in Jeddah and its relationship to organizational commitment from the teachers' point of view, and the degree of practice of organizational commitment by teachers in the Kingdom from the teachers' point of view, as well as to reveal the relationship between sustainable leadership and organizational commitment, and also to reveal the differences between the degree of practice of school principals in Jeddah for sustainable leadership in the light of the variables of gender and experience and the detection of differences in and the degree of perception of teachers in Jeddah applying organizational commitment in the light of the variables of gender and experience. To achieve the objectives of the study, a quantitative approach was followed that combines the survey and correlation methods. The sample of the study consisted of (612) male and female secondary school teachers. The researchers used the sustainable leadership questionnaire prepared by Kalvan (2015) and the organizational commitment questionnaire prepared by Ghali and Dahleez (2015). The results of the research showed that the general trend of school principals' practice of sustainable leadership is high from the teachers' point of view. The results also showed that the general trend of teachers' practice of organizational commitment was high. It was also found that there is a statistically significant positive relationship between sustainable leadership and organizational commitment. Also, the results showed that there were statistically significant differences in the degree of practicing sustainable leadership by school principals in Jeddah from the point of view of their teachers, due to the gender variable in favor of females. Also, there are no statistically significant differences in the degree of practice of sustainable leadership by school principals in Jeddah from the point of view of their teachers due to the variable of experience There are also statistically significant differences in the degree of teachers' perception of organizational commitment in Jeddah due to the gender variable in favor of females. There are also statistically significant differences in organizational commitment attributed to experience in favor of teachers with years of experience between 10-20 years.
Keywords: Sustainable Leadership; Organizational Commitment; Secondary School